Дослідження та розроблення енергоощадних вібраційних машин і процесів - Назаренко, Іван; Свідерський, Анатолій; Ручинський, Микола; Дєдов, Олег (КІНПАТРІ ЛТД, 2013)
The dynamics of such vibrosystems is in-process investigational on the example of vibratory grounds, multifat vibrooptions with the guided hydraulic drive, vibratory screen and vibrofluidizers forming of concrete wares of difficult form. Gain-frequency descriptions of such vibrosystems are investigational with limitations of vibrations with determination of areas of the proof mode motion.
Researches and development of energy-efficient vibratory machines and processes